Internationalization Knowledge: What, Why, Where, and When?. Issue 3 (September 2013) - Fletcher, Margaret; Harris, Simon; Richey, Robert Glenn
The acquisition of relevant knowledge plays a critical role in the internationalization process. Yet a complete understanding of internationalization knowledge (IK) remains largely unexplored in the international marketing literature. The authors develop a framework that distinguishes three categories of IK necessary for internationalizing firms to gain market entry, localize strategies, and organize international enterprise procedures. Employing a longitudinal qualitative analysis of ten internationalizing firms, this study examines (1) why firms need these IK categories, (2) where they source them, and (3) at what stage of international growth they are needed. The authors conclude by addressing implications for practice and recommend that managers should source the specific IK needed before it becomes critical.